Microsurgical Lymphatic Vessel Transplantation - Baumeister, Ruediger G. H.; Mayo, Weiss; Notohamiprodjo, Mike; Wallmichrath, Jens; Springer, Stephanie; Frick, Andreas (Journal of Reconstructive Microsurgery, 2016)
Background Lymphedema often arises after a regional interruption during cancer treatment, for example after lymph node resection the axilla or the groin. Lymphatic vessels as vascular grafts may overcome these lymphatic gaps.Method Experiments in rats and dogs were performed for developing this method. Volume measurements, lymphoscintigraphies, proof of patency by MRI and radiology as well as quality of life studies were performed in patients.Results Long-term follow-up studies revealed significantly reduced volumes, significant improvement of lymphatic outflow shown by lymphoscintigraphy, long-term patency of the grafts for more than 10 years, and improved quality of life after surgery compared with the situation with conservative treatment before surgery.Conclusion Vascular grafts using the patients own lymphatic vessels are able to successfully reconstruct a locally interrupted lymphatic pathway.
Keywords: lymphedema; lymphatic vessel; vascular graft; microsurgery